Graphic Novels for Multimodal Literacy and Reading Comprehension Development in an EFL Extensive Reading Course - Rahmi Munfangati; Maman Suryaman (JOLLT Journal of Languages and Language Teaching, 2026)
EFL students in Extensive Reading course often encounter reading comprehension difficulties due to limited vocabulary, insufficient inferential skills, and restricted exposure to authentic English texts. Although graphic novels have been recognized as engaging reading materials, limited research has examined their role in fostering multimodal literacy and reading comprehension in EFL Extensive Reading contexts. This study aimed to explore how graphic novels support multimodal literacy and reading comprehension among EFL students enrolled in an Extensive Reading course. A qualitative descriptive design was employed involving three undergraduate students from the English Language Education Study Program at Universitas Ahmad Dahlan. Participants were selected through purposive sampling based on their experience in reading graphic novels during the course. Data were collected through semi-structured interviews and analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings revealed that graphic novels facilitated reading comprehension by providing visual support for understanding context, emotions, vocabulary, and narrative structure. The multimodal features of graphic novels also increased students’ engagement, supported contextual reading strategies, and promoted the integration of visual and textual information. However, challenges were identified, including students’ overreliance on visual elements and differing perceptions regarding the contribution of graphic novels to critical thinking. The study concludes that graphic novels are effective multimodal resources for supporting multimodal literacy and reading comprehension in EFL Extensive Reading contexts. The findings suggest that teachers are encouraged to integrate graphic novels into Extensive Reading course while providing explicit guidance on interpreting visual and textual elements to maximize learning outcomes.